Our UK Natural Health Service - Bird, William (Socialmedicinsk tidskrift, 2012)
The UK led the Industrial Revolution that had a major impact in disconnecting people from nature. Two major acts of parliament in the 19th and 20th century were required to halt the contamination of water and air. However despite rising life expectancy and improvement in healthcare the rise in chronic disease is already causing more deaths than all other causes combined. This is likely to have a major negative impact on life expectancy in the future. Health inequalities appear to be major driver for ill health possibly by increasing chronic stress particularly amongst the poor. Contact with nature has been shown to offset this chronic stress. This paper explains how the UK Government have changed their policies in the past 10 years to embrace nature as a public health issue. Three UK schemes are then used to illustrate how people can be encouraged to reconnect with nature in communities healthcare and amongst employers.